(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This study aimed to assess the effects of educational music interventions which were delivered in situations outside the school setting. A systematic search was conducted in Scopus, PubMed and Google Scholar databases in order to analyze previously published research works on educational music interventions delivered in out-of-school settings. We scanned the online literature for articles with keywords like music intervention educational music therapy, music therapy and cancer patients, music therapy and anxiety, music therapy and depression. As a result of research conducted previously, there is compelling evidence that actively participating in educational music intervention can lead to a wide range of abilities exhibited by participants. In general, the results of the literature analysis show that educational music interventions have positive effects on patients' quality of life as well as their emotional well-being. In conclusion, educational music interventions have the potential to reduce negative emotional states and improve the quality of life for patients in various non-school settings, and appear to be a promising alternative to medications.